Numerical modeling of ventilation process and thermal status of the noise-heat protective housing of a gas-turbine plant on parallel computers - Trusov, Petr Valentinovich; Charntsev, Dmitriy Anatolievich (Computational Continuum Mechanics, 2012)
We study the thermal status of a noise-heat protective housing (NHPH), where a gas turbine plant (GTP) is located. The analysis of thermal conditions requires consideration of heat transfer caused by radiation emitted by the heated elements of the housing. In this paper, a mathematical model is proposed to calculate the rate and temperature of the air flow inside the NHPH, as well as the temperature of the NHPH wall-material, making allowance for radiation heat transfer. A parallel algorithm is designed for solving the cluster gas dynamic problem. The optimization problem is solved by applying the parallel domain decomposition method. Calculations are made for the NHPH of one of the available of gas-compressor units. The results confirm that the heat transfer caused by radiation should be taken into account in the solution of a solid-state thermal conductivity problem for NHPH walls. There is good agreement between the calculated temperatures and the temperatures measured at certain points on the external surface of NHPH walls.